2019
DOI: 10.1155/2019/9541485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic or Local Administration of Zoledronate on Implant Osseointegration: A Preclinical Meta-Analysis

Abstract: Objective This study aims to investigate the effect of systemically administrated zoledronate on bone-implant fixation in animal models. Methods We searched MEDLINE, Embase, and EBSCO for studies that explore the role of systemic or local zoledronate delivery in implant osseointegration in animal models. The Review Manager software was used to analyze selected studies by using the weighted mean difference random-effects model. Analytical data are mainly about bone ingrowth, such as bone-to-implant contact (BIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…In this condition, BIC% represents just the amount of bone present during implant installation. This explanation is in agreement with other studies, which suggested that a follow-up time of 6 weeks is too short, and more than 8 weeks of observation are necessary to detect a possible effect of pharmacological drugs on the interfacial implant–bone response [ 29 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this condition, BIC% represents just the amount of bone present during implant installation. This explanation is in agreement with other studies, which suggested that a follow-up time of 6 weeks is too short, and more than 8 weeks of observation are necessary to detect a possible effect of pharmacological drugs on the interfacial implant–bone response [ 29 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Cardemil et al revealed that a systemic single dose of ZOL in ovariectomized animals improved bone-to-implant contact [ 31 ]. Recently, He et al [ 29 ] reviewed the literature and described 10 preclinical studies that confirmed a possible effect of systemic ZOL administration on implant osseointegration. Consequently, the conclusion seems justified that intravenous ZOL can improve implant osseointegration in osteoporotic animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical studies have already been performed to study the effect of such treatments on peri-implant bone regeneration in both healthy and osteoporotic animal models [9,18,19,[33][34][35]. Despite existing evidence that single treatment with BPs or simvastatin can enhance bone formation around dental implants in healthy and osteoporotic animal models, only limited work has been dedicated toward the effect of combined administration of anti-resorptive and anabolic agents [22][23][24][25]36,37]. In addition, there is a wide variation in the route of administration of such pharmacological agents, the timing in relation to osteoporosis induction and subsequent implant placement, as well as implantation time.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistent observations can be partly explained by differences in the experimental design, type of drugs, administration route, dose, and evaluation periods. He et al [23] performed a preclinical meta-analysis to the effect of zolendronate administration on implant osseointegration, quantitatively assessing BIC% and BA%. They concluded that zolendronate administration generally increases BA%, but that for short implantation times (< eight weeks) the effect is less compared to long implantation times (> eight weeks).…”
Section: Discussionmentioning
confidence: 99%